The thermal and non-thermal components within and between galaxy clusters Abell 399 and Abell 401. Issue 4 (21st October 2022) - Radiconi, Federico; Vacca, Valentina; Battistelli, Elia; Bonafede, Annalisa; Capalbo, Valentina; Devlin, Mark J; Di Mascolo, Luca; Feretti, Luigina; Gallardo, Patricio A; Gill, Ajay; Giovannini, Gabriele; Govoni, Federica; et al.
ABSTRACT: We measure the local correlation between radio emission and Compton- y signal across two galaxy clusters, Abell 399 and Abell 401, using maps from the Low Frequency Array and the Atacama Cosmology Telescope + Planck . These data sets allow us to make the first measurement of this kind at ∼arcmin resolution. We find that the radio brightness scales as F radio ∝ y 1.5 for Abell 401 and F radio ∝ y 2.8 for Abell 399. Furthermore, using XMM–Newton data, we derive a sublinear correlation between radio and X-ray brightness for both the clusters (F_radio F_X^0.7 ). Finally, we correlate the Compton- y and X-ray data, finding that an isothermal model is consistent with the cluster profiles, y F_X^0.5 . By adopting an isothermal–β model, we are able, for the first time, to jointly use radio, X-ray, and Compton- y data to estimate the scaling index for the magnetic field profile, B ( r ) ∝ n e ( r ) η in the injection and re-acceleration scenarios. Applying this model, we find that the combined radio and Compton- y signal exhibits a significantly tighter correlation with the X-ray across the clusters than when the data sets are independently correlated. We find η ∼ 0.6–0.8. These results are consistent with the upper limit we derive for the scaling index of the magnetic field using rotation measure values for two radio galaxies in Abell 401. We also measure the radio, Compton- y, and X-ray correlations in the filament between the clusters but conclude that deeper data are required for a convincing determination of the correlations in the filament.